THE ECONOMIC IMPACT OF BITCOIN: IMPLICATIONS FOR FINANCIAL INCLUSION AND MARKET STABILITY IN INDIA - Pasha, Mahiboob (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Bitcoin, as the leading cryptocurrency, has reshaped the global financial landscape, introducing a decentralized form of currency that bypasses traditional banking systems. This paper examines the economic impact of Bitcoin on India’s financial ecosystem, exploring its potential to promote financial inclusion and its implications for market stability. The analysis addresses the dual nature of Bitcoin: as an asset fostering economic participation for the unbanked and underbanked, and as a source of volatility with potential risks to financial systems. Through a detailed examination of regulatory frameworks, economic data, and case studies, this paper highlights both the opportunities and challenges posed by Bitcoin. Recommendations for policy adaptations that balance innovation with financial security are also provided to ensure that India can leverage Bitcoin for economic growth without compromising market stability.